THE CATEGORIES OF «BEAUTY» AND «HOLISM» IN THE CONTEXT OF HUMAN EXISTENCE - Крилова, С. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Beauty is realized through the categories «wholeness «,»entelechy» and «holism» and analyzed as both an existential and social phenomenon. Beauty is treated as an entity, passed through uniqueness of human presence in the world, and therefore as a new quality of holism.